EP1351 Inguinofemoral lymphadenectomy technique. (1st November 2019) - Altin, D; Taskin, S; Ortac, F
Abstract : Introduction/Background: For all vulvar cancer patients with tumour diameter greater than 2 cm and more than 1 mm of stromal invasion, inguinofemoral lymphadenectomy is indicated. In this video we present inguinofemoral lymphadenectomy technique with a patient with vulvar squamous cell cancer. Methodology: A linear incision made 1 cm above and parallel to the groin crease starting 3 cm distal and medial to the anterior superior iliac spine and ending below the superficial inguinal ring. The borders of the operation are sartorius muscle laterally, adductor longus muscle medially and inguinal ligament superiorly. The inguinofemoral lymph nodes are divided into superficial and deep. The superficial lymph nodes are above the fascia lata and the deep nodes lye below the fascia lata and within the femoral sheath. To remove the superficial nodes, incision is carried through the subcutaneous tissues to the Camper's fascia. The dissection should not be too close to the skin flaps as flap necrosis may develop. The fascia is incised and grasped with forceps for traction, and the fatty tissue between it and the fascia lata is removed. Usually the dissection is carried from lateral to medial and superior to inferior. Care should be taken to identify and preserve the great saphenous vein, which is superficial to the fascia of the medial thigh. To access the deep nodes, an incision is made through the cribriform fascia. Lymph nodes are always situated medial to the femoral vein in the opening of fossa ovalis. The proximal deep femoral node (node of Cloquet) is removed from the femoral triangle. The incision is closed in layers. Results: not applicable Conclusion: not applicable Disclosure: Nothing to disclose